Application of improved cutterhead technology of shield machine in anchor cable zones - Lin, Yunhong; Cao, Guoxu; Guo, Xiaodong (Frontiers in Earth Science, 2025)
The shield crossing an anchor cable zone can cause the anchor cable to wrap around the cutter, creating construction problems. To address this issue, we developed an improved cutterhead technology for the shield machine which was successfully used during the Zhengzhou Metro Line four tunnel project that crossed a large anchor cable zone. Our research outlines the technology’s configuration and provides a detailed analysis of the tunneling parameters in the anchor cable section. This innovative technology directly cuts anchor cables during construction and improves both the shield machine and tunneling parameters.